The importance of a seasonal ice zone and krill density in the historical abundance of humpback whale catches in the Southern Ocean - Cotte, Cedric; Guinet, Christophe (J. Cetacean Res. Manage., 2020)
Humpback whale populations in the Southern Hemisphere were dramatically reduced by the whaling industry. A comprehensive whaling dataset was used in an analysis of circumpolar abundance of humpback whale catches relative to contemporary densities of its preferred prey, Antarctic krill, and to a major dynamic feature of the marine ecosystem, the summer seasonal ice zone (SSIZ) derived from southernmost whaling locations. The circumpolar abundance of catches derived only from pelagic data, i.e. about 30% of the total humpback whale catches in the Southern hemisphere, was found to be only marginally related to krill density. However, the total abundance of catches – from pelagic operations and land stations, from high and low latitudes – was found to be more related to SSIZ than to krill density, especially when excluding the highly dynamic west Atlantic region where the circulation probably drives the ecosystem. A large SSIZ is likely to provide a favourable feeding ground for humpback whales, given their high energy requirements and because of its predictability and the prey aggregation processes occurring there.